S-Shaped Wide Excision with Primary Closure for Extensive Chronic Pilonidal Sinus Disease. (2nd June 2014) - Karaman, Kerem; Ozturk, Safak; Tugmen, Cem; Kebapcı, Eyup; Dogan, Sait Murat; Unver, Mutlu; Olmez, Mustafa; Aydin, Cengiz
Abstract : Background . The management of complex pilonidal sinus disease (PSD) with multiple pits on and beside the natal cleft is variable, contentious, and problematic. Wide excision of the sinus and reconstruction of the defect using different flap techniques have become more popular in recent years. Case Report . We report a case with a complex chronic PSD to which we applied primary closure after S-shaped wide excision. The patient's postoperative course was uneventful, and at the end of one-year followup he is now disease-free and comes for routine checkups. Conclusion . The simplicity of the technique and the promising results support the applicability of the S-shaped wide excision in chronic bilaterally extended large PSDs. Further studies entailing large patient populations are needed to reach a definite conclusion.